Right-wing populism and gender : European perspectives and beyond - Dietze, Gabriele; Roth, Julia (Gender studies (Bielefeld, Germany), 2020)
While the field of research in right-wing populism has recently been blossoming and is expanding, a systematic look into the interface of right-wing Populism and Gender is still missing, even though gender issues are omnipresent in discourses of the radical right ranging from "ethnosexism" against immigrants, to "anti-genderism". The volume seeks to strengthen the analysis of the intersection of gender and race as constitutional for radical right discourse. The contributions investigate from different European perspectives the ways in which gender is used as an arena and as an epistemological platform for the ordering and hierarchization of political objectives